Grid parity analysis of distributed PV generation using Monte Carlo approach: The Brazilian case. (November 2018) - Pillot, Benjamin; de Siqueira, Sandro; Dias, João Batista
Abstract: We have conducted a grid parity analysis of distributed PV generation in Brazil through the use of a probabilistic Monte Carlo approach. Essentially, we have derived the probability distribution of the levelized cost of electricity (LCOE) for both PV and grid electricity. We have thus assessed how likely grid parity will occur with respect to system's nominal power and financing scheme in a net metering framework, by computing the cumulative probability for which the LCOE difference is nonnegative: P ( Δ LCOE ≥ 0 ) . Regarding southern Brazil, it appears that economic viability of many residential grid-connected PV systems in operation is far from guaranteed, due to the need for substantial own capital and nominal capacity. 4-kW systems might be viable ( P ( Δ LCOE ≥ 0 ) = 0.82 ) but only by relying on equity financing, while small systems around 2 kW will not ( P ( Δ LCOE ≥ 0 ) ≤ 0.3 ). When debt financing is considered however, merely systems with nominal capacity above 7 kW present significant confidence levels ( P ( Δ LCOE ≥ 0 ) > 0.95 ). Eventually, it is outlined that electric company, state tax policy and consumption class are the effective leverages when assessing whether cost of distributed PV generation shall reach parity in the country. Highlights: Grid parity for distributed PV is analyzed through a probabilistic approach. Grid and PV LCOE probability distributions are computed. Grid parity likelihood is inferred according to nominal power and financing scheme. A Pareto-like method is proposed to assess debt financing influence on grid parity. In Brazil, electric company, tax policy and consumption class govern grid parity.